25th Southern Biomedical Engineering Conference 2009, 15 17 May 2009, Miami, Florida, USA - McGoron, Anthony J.; Li, Chen-Zhong.; Lin, Wei-Chiang. (IFMBE Proceedings, 2009)
This volume presents the contributions of the 25th Southern Biomedical Engineering Conference, held in May 2009 in Miami, Florida. The papers of this Proceedings volume present new developments in theory, concept, application, and techniques in all facets of Biomedical Engineering. The broad spectrum of topics includes: Optical Imaging, Instrumentation, Biomaterials-Mechanical, Rehabilitation, Image Processing, Orthopedics, Nanomaterials, Algorithms Neural, Sensors, Tissue Engineering, Signals and Systems, Cardiovascular Systems, and Drug Delivery